PERENCANAAN KOMUNIKASI PUBLIK DP3AP2KB KOTA TANGERANG DALAM UPAYA PEMBERDAYAAN PEREMPUAN MENANGGULANGI PERSOALAN LINGKUP KEMISKINAN KELUARGA DIMASA PANDEMI COVID-19 (STUDI KASUS PROGRAM P2WKSS) - Dika Mulqilfin Pratama; Lina Wati; Ari Suseno (Interpretasi: Communication & Public Relations, 2022)
With this, the results of the work that have been made by researchers regarding the P2WKSS program organized by DP3AP2KB, see how to communicate the program, and see the implementation of programs that have been held. By using Cultip & Center Theory, there are 4 indicators, namely, Fact Finding, Planning, Communication, and Evaluation. The method used in This research is qualitative, with a case study approach. Data collection techniques are observation and interviews with the object which is the organizer. The results of writing from researchers that there is still a need for communication planning carried out by DP3AP2KB to be able to invite the public to want to participate in government programs to help improve the family economy that is happening at this time, through the P2WKSS program, the community can increase awareness that they live their lives from various aspects, namely, health, economy, education, and environment in the surrounding area.